PHYLOGENETICAL STUDY OF WILD BANANA SPECIES (Musa L.) IN SULAWESI INFERRED FROM INTERNAL TRANSCRIBED SPACER REGION OF NUCLEAR RIBOSOMAL DNA SEQUENCES - Lulut Dwi Sulistyaningsih; Rita Megia; Elizabeth Anita Widjaja (SEAMEO BIOTROP, 2014)
Study to determine the phylogenetic relationship of wild banana species (Musa) in Sulawesi based on the ITS regions sequences has been done. A total of 28 samples including 16 ITS sequences from GeneBank were used. Species of Ensete and Musella were incorporated as an outgroup. Total DNA was extracted by the modified CTAB. ITS-5 and ITS-4 primers were used to amplify the ITS regions. Data sequences were edited by ChromasPro and were aligned by Muscle software.Some unique nucleotides were found in M. balbisiana, M. itinerans, and M. textilis sequences. Strict consensus tree revealed from Maximum Parsimony (MP) as well as Bayesian analysis showed Musa textilis was separated from other taxa in which M. textilis become as the basal sister to M. balbisiana. By using MP analysis, M. itinerans together with M. acuminata ssp. banksii, M. acuminata var. tomentosa, and M. celebica placed in the same clade, whereas Bayesian analysis showed M. itinerans was separated and placed in different clade.